Pengembangan Lembaga Pendidikan Islam melalui EduVision Strategika dalam Pembentukan Karakter di Pondok Pesantren Miftahul Ulumi Syar’iyah Canduang - Kelana, Saputri; Redwan, Muhammad Hafis bin; Yetri, Yetri; Ilmi, Darul (Journal of Civic Education, 2025)
This study aims to analyze operational strategies and social relations in the development of Islamic educational institutions through the EduVision Strategika approach at the Miftahul Ulumi Syar'iyyah Canduang Islamic Boarding School. The research employs a qualitative case study method, with data collected through in-depth interviews, participatory observation, and documentary analysis involving 15 key informants. The findings reveal that the boarding school's development success is determined not only by operational factors such as integrative curriculum planning, participatory human resource management, and Islamic value based governance but also by strong social cohesion among leaders, teachers, students, alumni, and the surrounding community. Thus, this is inline with the internalization of civic education in Islamic education institution. The EduVision Strategika approach serves as an integrative model that combines an Islamic value-based educational vision, managerial innovation, and social network strengthening, enabling Islamic boarding schools to adapt to modern dynamics without abandoning Islamic traditions. The study offers practical contributions to the development of Islamic educational institution strategies and civic educations that effectively balance operational and social aspects, providing a sustainable development model for contemporary Islamic education.